The Political and Academic Fields and the Discourse on Special Education - Sirleine Brandão de Souza (Universidade Federal do Rio Grande do Sul, 2020)
The objective of this study was to analyze and discuss permanence and ruptures in the identity of special education and the close relationship between the academic field and educational policies. The contributions of Pierre Bourdieu were used, specifically the concepts of language and field and as a methodology for the analysis of the narratives produced in publications of the Brazilian Journal of Special Education. It was concluded that the relationship between these fields reflects the constant search of a set of researchers to more carefully specify the field of special education and the temporal coexistence of similar, distinct and antagonistic perspectives, configuring the field with a multifaceted identity, reflecting the contradictory movement of society and social policies.